2021
DOI: 10.3390/s21248503
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Machine Learning Models and Survival Analysis for COVID-19 Prognosis Based on Hematochemical Parameters

Abstract: The coronavirus disease 2019 (COVID-19) pandemic has affected hundreds of millions of individuals and caused millions of deaths worldwide. Predicting the clinical course of the disease is of pivotal importance to manage patients. Several studies have found hematochemical alterations in COVID-19 patients, such as inflammatory markers. We retrospectively analyzed the anamnestic data and laboratory parameters of 303 patients diagnosed with COVID-19 who were admitted to the Polyclinic Hospital of Bari during the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…Comparing our model with other decision tree models, it can be observed that our model has an accuracy similar to that of Migriño (81.5%) [ 28 ], but lower than that of Altini et al [ 29 ] and Naseem et al [ 30 ], which were both higher than 85%. It is noteworthy that our model specificity was low when compared to other research [ 29 , 30 ]. On the other hand, the model has a 89,16% F-score, which is higher than another machine learning model that predicted outcomes in patients with COVID-19 [ 28 ].…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Comparing our model with other decision tree models, it can be observed that our model has an accuracy similar to that of Migriño (81.5%) [ 28 ], but lower than that of Altini et al [ 29 ] and Naseem et al [ 30 ], which were both higher than 85%. It is noteworthy that our model specificity was low when compared to other research [ 29 , 30 ]. On the other hand, the model has a 89,16% F-score, which is higher than another machine learning model that predicted outcomes in patients with COVID-19 [ 28 ].…”
Section: Discussionmentioning
confidence: 58%
“…A machine learning approach, the decision tree model, was used to analyze the clinical data of hospitalized COVID-19 patients to establish an efficient prognosis [ 29 ]. In this study, we used the clinical, demographic, and blood chemistry parameters of the patients in order to predict two possible outcomes: discharged alive, or transferred to ICU or death, whichever was first.…”
Section: Discussionmentioning
confidence: 99%
“…Early identification of patients at higher risk for superinfections or other complications, before significant increases in CRP and LDH levels, could facilitate more efficient treatment strategies and improve patient outcomes. [66]. These models, particularly ensemble models, have demonstrated high accuracy and AUC values in predicting patient outcomes, such as recovery, ICU admission, and death.…”
Section: Serum Inflammatory Biomarkersmentioning
confidence: 99%
“…Numerous researchers have employed diverse predictive indicators in their investigation of COVID-19 to evaluate the prognosis of the disease's ultimate clinical outcome. These predictive indicators comprise blood samples, electrocardiograms, imaging data (CT, XCR), respiratory parameters, clinical symptoms, and other relevant information [28][29][30][31][32][33][34][35] . The concluding indicators of the study were also varied, with a primary focus on the severity of the illness, the risk of mortality, the actual mortality rate, the length of hospitalization, and other relevant factors.…”
Section: The Implementation Of Ai In Forecasting the Medical Conditio...mentioning
confidence: 99%